If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(z + -3) = 5 + 4z Reorder the terms: 3(-3 + z) = 5 + 4z (-3 * 3 + z * 3) = 5 + 4z (-9 + 3z) = 5 + 4z Solving -9 + 3z = 5 + 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. -9 + 3z + -4z = 5 + 4z + -4z Combine like terms: 3z + -4z = -1z -9 + -1z = 5 + 4z + -4z Combine like terms: 4z + -4z = 0 -9 + -1z = 5 + 0 -9 + -1z = 5 Add '9' to each side of the equation. -9 + 9 + -1z = 5 + 9 Combine like terms: -9 + 9 = 0 0 + -1z = 5 + 9 -1z = 5 + 9 Combine like terms: 5 + 9 = 14 -1z = 14 Divide each side by '-1'. z = -14 Simplifying z = -14
| 24=6(x+-6)-x | | 5x+6x-2=20 | | 8x+13+2x+7=180 | | -2.6d-0.49=1.79 | | 2-2-2-2-2-2-2+2+x=3 | | p-400=1230 | | 4x-6x-40=0 | | 2-2-2-2-2-2-2-2-2=2 | | 6n-18=4n | | an=7+(n-1)(7) | | x-13=3x-27 | | X(x+10)=90 | | 0.06(y-9)+0.08y=0.18y-0.2 | | 13x+12=8x+7+4x+14 | | x-54=27 | | 55x+200=20+65x | | lnx=0.375 | | 6x^2+24=25x | | 27=6(9d-8) | | t+400=1230 | | 5x-9+7=-3 | | 10d+25q=45 | | sn=(n-2)180 | | M-3=23.8 | | M+z=bx | | 2.77= | | r-0.58=8.92 | | X^2-10=2x | | -2-(-3x-8)=4(-8z-7)+5 | | A=5.7 | | 7(p+2)+5p=60 | | 5x-9+7=3 |